Presenting a Model of Co-Dependency in Women with Addicted Spouses based on their Self-Differentiation with the Mediating Role of Emotional Cognitive Regulation - Karimi Haresabadi, Azam; Mohammadi shirmahaleh, Fatemeh; Rafezi, Zohreh; GholamiTooranposhti, Marziyeh; Peyvandi, Parisa (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to present a model of co-dependency in women with addicted spouses based on their differentiation with the mediating role of emotional cognitive regulation. Methods: The research method is cross-sectional correlation. The statistical population of this study consisted of all women with drug-addicted wives who referred to counseling centers, health centers and addiction treatment camps and meetings in Tehran in 1400, of which 188 people by cluster sampling they were selected in stages. In this study, tools of co-dependency (Span & Fisher, 1990), self-differentiation (Skorn and Friedlander, 1998) and cognitive-emotional regulation (Garnfsky and Craig, 2006) were used. Amos-V8.8 software were used to analyze the data. Structural equation modeling was also used to answer the research hypotheses. Findings showed that the model has a good fit. Results: The results also showed that self-differentiation had a significant direct negative effect on co-dependency (P <0.01). Self-differentiation had a direct positive effect on adaptive cognitive emotion regulation strategies (P <0.01). Adaptive strategies for cognitive emotion regulation have a direct and negative effect on co-dependency (P <0.01). The results showed that non-adaptive cognitive emotion regulation strategies had a direct and positive effect on co-dependency (P <0.01). Self-differentiation also had an indirect effect on codependency through cognitive emotion regulation (β = -0.181; P = 0.01). Conclusion: Structural equation modeling fit indices confirmed the overall research model and the direct and indirect effects between the research variables were confirmed. Therefore, according to the results, it can be said that co-dependency is an important variable in predicting self-differentiation and cognitive regulation of emotion.